Penerapan Media Pembelajaran Flashcards untuk Meningkatkan Hasil Belajar Al-Qur’an Hadis Materi Hukum Bacaan Idzhar - Siti Nuraisah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This research is motivated by the findings of the learning process that has an impact on student learning outcomes, including learning that is still centered on the teacher and the use of instructional media is less than optimal and only fixated on textbooks. This study aims to improve the learning process by using flashcards media. This research is a classroom action research carried out collaboratively between the teacher and the researcher which is carried out in two actions in each cycle. The subjects of this study were 20 students of class IV MI At-Taqwa. The data collection tools used were evaluation test sheets, student observation sheets, teacher observation sheets and activity photos. The data in this study were in the form of quantitative and qualitative data which were analyzed using quantitative descriptive analysis. The research results obtained are an increase in student learning outcomes. The average score of the students before the action was taken was 33.75 with the percentage of students' completeness reaching 33.75%. In cycle I, the class average value obtained was 75.00 with a percentage of student completeness reaching 75%. In cycle II the class average value obtained was 94.25 with the percentage of student completeness reaching 95%. The results of the study show that the implementation of learning using Flashcard media can improve student learning outcomes in the Al-Qur'an Hadith subject in class IV MI At-Taqwa.